Theoretical investigation on the dissociation of (R)‐benzoin catalyzed by benzaldehyde lyase. Issue 6 (5th November 2013) - Zhang, Jing; Sheng, Xiang; Hou, QianQian; Liu, Yongjun
<x xml:space="preserve">Abstract</x> Benzaldehyde lyase (BAL) is a versatile thiamin diphosphate (THDP)‐dependent enzyme with widespread synthetic applications in industry. Besides lyase activity, BAL also performs the functions as carboligase and decarboxylase. Unlike many other THDP‐dependent enzymes, the active center of BAL is devoid of any acid‐base amino acid residues except Glu50 and His29, and therefore, the catalytic mechanism of BAL is unusual. In this article, the dissociation mechanism of (R)‐benzoin to benzaldehyde catalyzed by BAL has been studied by using density functional theory method. The calculation results indicate that the whole reaction consists of four elementary steps, and at least two steps contribute to rate‐limiting. A big difference with other THDP‐dependent enzymes is that, in the first stage of the reaction, the ligation of substrate and THDP ylide is not companied by proton transfer, and in the subsequent transition states and intermediates, the carbonyl oxygen always exists in the form of anion. Gln113, His29, and 4′‐amino group of THDP are found to have the function to stabilize the transition states and intermediates. His29 acts as the proton acceptor in step 2 and proton donor in step 3 using one water molecule as mediator. © 2013 Wiley Periodicals, Inc.